Synthesis of Novel bis-spirooxindoles Catalyzed by Magnetic Cobalt Ferrite Encapsulated MCM-41@MgO as a Solid Base - Mohammadi, Somaye; Naeimi, Hossein (Current Organic Synthesis, 2021)
Aims and Objective: Synthesis of novel bis-spirooxindoles was carried out from isatins, two equivalents of malononitrile, and various derivatives of cyclohexanones. Background: A facile one-pot and four-component reaction was investigated for the synthesis of novel bisspirooxindoles from different derivatives of isatins, two equivalents of malononitrile and various derivatives of cyclohexanone in the presence of magnetic CoFe2O4@MCM-41@MgO NPS catalyst under mild conditions. Materials and Methods: Firstly, the magnetic CoFe2O4@MCM-41@MgO was prepared in three steps. Afterwards, the CoFe2O4@MCM-41@MgO was used as a base catalyst for the one-pot synthesis of bisspirooxindoles. Results and Discussion: The procedure exhibited several benefits, an excellent yield of products, short reaction times, reusability, and recyclability of the nanocatalyst. Conclusion: The structure of nanocatalyst was recognized by FT-IR, XRD, VSM, SEM, BET, and EDX techniques, and the structure of the organic products was determined by melting point, FT-IR, 1H NMR, 13C NMR, Mass spectra, and C.H.N analyses.
Keywords: C.H.N analyses